The influence of trust, usefulness, and security on the intention to use the ferizy application for ro-ro ferry ticket booking in Batam - Reza Putri Geni; Alice Erni Husein (Trigin Publisher, 2025)
This study examines the influence of Trust, Usefulness, and Security on the Intention to Use the Ferizy application for Ro-Ro ferry ticket reservations in Batam. As digital platforms increasingly shape transportation services in Indonesia, understanding user perceptions becomes crucial for enhancing adoption and sustaining long-term engagement. Using a quantitative approach, data were collected through structured questionnaires distributed to active Ro-Ro ferry users. The results show that Trust, Usefulness, and Security each have a positive and significant effect on Intention to Use, while the simultaneous F-test confirms that these three variables collectively contribute substantially to explaining user intention. Descriptive findings indicate that users perceive Ferizy as highly useful, particularly in facilitating faster and more efficient ticket reservations. Trust levels are also relatively high, supported by perceptions of system credibility and transparent service information. Security emerges as a critical determinant, as users express confidence in the protection of personal data and the safety of digital transactions. The variable measuring Intention to Use records the highest average score, reflecting strong user motivation to continue utilizing the application. These findings underscore the necessity for digital service providers to strengthen system reliability, functional benefits, and robust security mechanisms, while also offering theoretical contributions to consumer behavior research within digital service adoption in Indonesia.